2018
DOI: 10.1080/09546634.2018.1468068
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil therapy in adult patients with recalcitrant atopic dermatitis

Abstract: Oral MMF may be an effective drug in AD. Due to its good safety profile, it may be recommended as a first-line systemic therapy, or successive to CSA in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Some case reports or uncontrolled clinical trial data from adults indicate that MMF could be effective in dermatitis. 127,128,129,130,131 In an observer-blinded randomized controlled trial in 55 patients, a lower dose CSA (3 mg/kg/d) was found to be equally effective to oral MMF (EC-MPS, 1440 mg/d) as a maintenance therapy for severe dermatitis during a maintenance phase of 30 weeks and a 12-week follow-up period. 112 The MMF group had a slower onset of action with 29% of the MMF patients requiring short courses of systemic glucocorticoids compared to none in the CSA group.…”
Section: • Methotrexate (Mtx) Patients Receiving Mtxmentioning
confidence: 99%
“…Some case reports or uncontrolled clinical trial data from adults indicate that MMF could be effective in dermatitis. 127,128,129,130,131 In an observer-blinded randomized controlled trial in 55 patients, a lower dose CSA (3 mg/kg/d) was found to be equally effective to oral MMF (EC-MPS, 1440 mg/d) as a maintenance therapy for severe dermatitis during a maintenance phase of 30 weeks and a 12-week follow-up period. 112 The MMF group had a slower onset of action with 29% of the MMF patients requiring short courses of systemic glucocorticoids compared to none in the CSA group.…”
Section: • Methotrexate (Mtx) Patients Receiving Mtxmentioning
confidence: 99%
“…Monitoring of liver function and blood cell counts is necessary during the treatment with MTX and AZA. MMF efficacy is comparable to that of CsA in the treatment of AD [42]. The treatment starts at the dose of 1-2 g/day.…”
Section: Dupilumabmentioning
confidence: 89%
“…W trakcie leczenia MTX oraz AZA konieczne jest monitorowanie czynności wątroby i morfologii krwi. MMF ma udowodnioną skuteczność w leczeniu AZS, porównywalną z CsA [42]. Leczenie rozpoczyna się od dawki 1-2 g/dobę.…”
Section: Leczenie Ogólne Poza Wskazaniami Rejestracyjnymiunclassified
“…Mycophenolate mofetil (MMF) is an immunosuppressive drug administered in the prophylaxis against acute rejection after solid organ transplantation as well as in autoimmune diseases [ 1 ], nephrotic syndrome [ 2 , 3 ], and atopic dermatitis [ 4 ]. The MMF active moiety, mycophenolic acid (MPA), is characterized by complex and variable pharmacokinetics and high serum albumin binding (97–99%) [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%